Advances in cardiac magnetic resonance imaging of congenital heart disease. - Driessen, Mieke M P; Breur, Johannes M P J; Budde, Ricardo P J; van Oorschot, Joep W M; van Kimmenade, Roland R J; Sieswerda, Gertjan Tj; Meijboom, Folkert J; Leiner, Tim (Pediatric Radiology, 2015)
Due to advances in cardiac surgery, survival of patients with congenital heart disease has increased considerably during the past decades. Many of these patients require repeated cardiovascular magnetic resonance imaging to assess cardiac anatomy and function. In the past decade, technological advances have enabled faster and more robust cardiovascular magnetic resonance with improved image quality and spatial as well as temporal resolution. This review aims to provide an overview of advances in cardiovascular magnetic resonance hardware and acquisition techniques relevant to both pediatric and adult patients with congenital heart disease and discusses the techniques used to assess function, anatomy, flow and tissue characterization.